Penggunaan Blended Learning Mata Pelajaran IPA Terhadap Peningkatan Hasil Belajar Siswa Pada Materi Kemagnetan - Prio Sigit Nugroho; Devi Septiani (Universitas Sarjanawiyata Tamansiswa, 2022)
The problem encountered in class IX learning science is the low learning outcomes of students, especially on magnetic material. This can be found when looking at the list of values, most of which are under the Minimum Completion Criteria (KKM), which is 68. The purpose of this study is to find out whether Blended Learning learning is able to improve learning outcomes of students, especially on magnetic material in class IX middle schools first. This research is a Classroom Action Research (PTK), the sample in this study is class IX.2, amounting to 20 people. Research data in the form of student learning outcomes were taken using test and observation techniques, the test results obtained an average value of 56.80 to 85.60 with SD = 11.35 and 95% of students scored above the minimum completeness criteria (KKM). The trend of increasing student activity can be seen from cycle I to cycle II. The conclusion of this research is that Blended Learning can improve student learning outcomes in the discussion of magnets.